2016
DOI: 10.1038/srep19849
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analyses of how tubule occlusion and advanced glycation end-products diminish strength of aged dentin

Abstract: In clinical dentistry, since fracture is a major cause of tooth loss, better understanding of mechanical properties of teeth structures is important. Dentin, the major hard tissue of teeth, has similar composition to bone. In this study, we investigated the mechanical properties of human dentin not only in terms of mineral density but also using structural and quality parameters as recently accepted in evaluating bone strength. Aged crown and root dentin (age ≥ 40) exhibited significantly lower flexural streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 52 publications
0
41
0
Order By: Relevance
“…Interestingly, this correlation was also seen in tooth dentin [85]. Thus, the BAp c-axis orientation is a potent parameter for bone quality and may be useful in evaluating and predicting mechanical properties of various types and conditions of biological hard tissues.…”
Section: Contribution Of the Bap C-axis Orientation To Bone Mechanicamentioning
confidence: 73%
See 1 more Smart Citation
“…Interestingly, this correlation was also seen in tooth dentin [85]. Thus, the BAp c-axis orientation is a potent parameter for bone quality and may be useful in evaluating and predicting mechanical properties of various types and conditions of biological hard tissues.…”
Section: Contribution Of the Bap C-axis Orientation To Bone Mechanicamentioning
confidence: 73%
“…The relationships between BAp/collagen orientation and other bone quality parameters introduced in this review -collagen chemistry and osteocytes -are now becoming clarified. A negative relationship between the amount of AGE cross-links and the degree of BAp orientation is also suggested [85]. Moreover, synchronous alteration of anisotropic features in osteocyte network and BAp/collagen arrangement was reported [83,84,153,154].…”
Section: Conclusion and Future Directionmentioning
confidence: 93%
“…27 As mentioned above, the decrease in the volumetric fraction and diameter of the tubules induces the increase of the shear modulus (G) and Young's modulus values. Considering the data obtained with the use of the analytical homogenization procedure, we could state that within the same layer of dentin an increase of the tubules' diameter (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…27 At the same time, the ageing of the dentin, with the obturation of the tubules, resulting from higher mineralization, could diminish the flexural strength. Panfilov et al showed higher tensile strength of mature rather than teenage dentin (549.5 ± 26.9 MPa vs 445.2 ± 30.9 MPa, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent multi-variable analysis of the reduction in flexure strength of dentin with age, Shinno et al, [75] reported that the changes were correlated with increasing Advanced Glycation End (AGE) product content, and increasing mineral density. AGEs are intra- and interfibrillar nonenzymatic crosslinks that develop through glycation [76].…”
Section: Agingmentioning
confidence: 99%